Analisis Penggunaan Metode Bercerita Islami dalam Menanamkan Nilai Adab Makan pada Anak Usia Dini di KB Permata Sari Desa Bantan Tua - Mariya Mariya; Susi Suharni; Mufaro’ah Mufaro’ah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to examine how effective the Islamic storytelling method is in instilling eating etiquette values ​​in young children at KB Permata Sari, Bantan Tua Village. In this context, eating etiquette includes behavior such as praying before and after eating, maintaining cleanliness, and adopting polite attitudes when eating. The Islamic storytelling method was chosen because it was considered capable of conveying Islamic values ​​in a way that was interesting, simple and easy for children to understand. Through stories, these values ​​can be conveyed subtly and arouse children's curiosity, so that it is easier for them to remember and internalize these values. The results of this research show that the Islamic storytelling method is effective in shaping children's understanding and behavior regarding good eating etiquette. After being given lessons through stories, children show a deeper understanding of the importance of eating etiquette, and begin to implement behavior according to the values ​​conveyed, such as praying before eating, maintaining cleanliness, and eating with a polite attitude. These findings confirm that the Islamic storytelling method not only introduces the values ​​of eating etiquette, but also helps form positive habits in children on an ongoing basis.